Differential allocation: tests, mechanisms and implications. - Sheldon, B (2000)
Differential allocation occurs when reproductive investment is influenced by mate attractiveness. Recently, wide-ranging empirical support for differential allocation has been obtained. These data suggest that mates can affect the payoffs from reproduction, thus making sacrifices of reproductive value worthwhile when breeding with an attractive mate. As an example of an adaptive parental effect, the existence of differential allocation has some interesting implications for empirical studies of sexual selection and for predicting evolutionary responses to selection.